1) or let b_n = a_n+1
So that the recurrence looks like b_{n+1} = 2b_n
1)find the nth term of the sequencesuch that
2)Find the nth term of the sequence such that
3)Find the nth term of the sequence such that
then Calculate
4)Find the n th term of the sequence such that
5)Find the n th term of the sequence such that
first one
a_n=3.2^{n-1}-1
\texttt{the characteristic polynomial here is } 1-2x \\ hence \\ a_n=coefficient (x^n,(1-2x)^{-1}\left(a_1x +x^2 +x^3+....x^n+.\infty \right) \\ hence \\ a_n =1+2+2^2+2^3+.......+2^{n-2}+a_1.2^{n-1} \\ \Rightarrow a_n=2^{n-1}-1+2^{n-1}.2=\boxed{3.2^{n-1}-1}
3rd one
a_n=\sum_{k=1}^{n}{a_k}-\sum_{k=1}^{n-1}{a_k} \\ a_n=3n(n+1)\\ \frac{1}{a_n}=\frac{1}{3}(\frac{1}{n}-\frac{1}{n+1})
1) or let b_n = a_n+1
So that the recurrence looks like b_{n+1} = 2b_n
ya akari u r correct :)
try oder ones also ....i added 5th one
btw i had an approch for 1st one ....but much lengthier than generating polynomials
a_{n+1} = \frac{a_n}{2} + \frac{n^2-2n-1}{n^2(n+1)^2} = \frac{a_n}{2} + \frac{2}{(n+1)^2} - \frac{1}{n^2}
\Rightarrow a_{n+1} - \frac{2}{(n+1)^2}= \frac{1}{2} \left(a_n - \frac{2}{n^2} \right)
So if you define a sequence {bn} as b_n = a_n - \frac{2}{n^2} then this sequence obeys the recurrence b_{n+1} = \frac{b_n}{2}
Q4. nan = (n-1)Sn
(n-1)an-1 = (n-2)Sn-1
Subtracting,
n(an - an-1) + an-1 = (n-1)an + Sn-1
=> an - (n-1)an-1 = (n-1)an-1/(n-2)
=> an = (n-1)2an-1/(n-2) = (n-1)2(n-2)(n-3)(n-4)....2.a2
also 2a2 = 1 + 1 + a2
=> a2 = 2
=> an = 2(n-1)(n-1)!
quite long i guess
5) Rewriting the recurrence as n^3 a_n = (n-1)^3 a_{n-1} + n(n-1)
Let b_n = n^3 a_n
Then we have the recurrence b_n -b_{n-1} = n(n-1)
This can be summed up telescopically to arrive at
b_n-b_1 = \sum_{k=2}^n k^2-k = \sum_{k=1}^n k^2-k = \frac{n(n^2-1)}{3}
b1=0 and hence a_n = \frac{(n^2-1)}{3n^2}
continuing from prophet sir's # 10 post
b_{n}=2b_{n+1}
b_{n-1}=2b_{n}
b_{n-2}=2b_{n-1}=4b_{n}=2^{2}b_{n}
\Rightarrow b_{n-k}=2^{k}b_{n}
\Rightarrow b_{n-(n-1)}=2^{(n-1)}b_{n}
\Rightarrow b_{1}=2^{(n-1)}b_{n}
\Rightarrow b_{n}= \frac{b_{1}}{2^{(n-1)} }
also\;\;\; b_{n}= a_{n}-\frac{2}{n^{2}}
b_{1}= a_{1}-\frac{2}{1}= -1
a_{n}-\frac{2}{n^{2}}= \frac{-1}{2^{n-1}}
a_{n}=\frac{2}{n^{2}}+\frac{-1}{2^{n-1}}= \frac{2^{n}-n^{2}}{2^{(n-1)}n^{2}}
ya qwerty thats correct :)
btw u can do this
\\\texttt{after \; u\; got\; this}\\ a_{n+1}-\frac{2}{(n+1)^{2}}={1\over 2}\left(a_{n}-\frac{2}{n^{2}}\right)\\ \Rightarrow \prod_{k=1}^{k=n-1}\left ( a_{k+1}-\frac{2}{(k+1)^{2}} \right )=\prod_{k=1}^{k=n-1}\left ( {1\over 2}\left(a_{k}-\frac{2}{k^{2}}\right) \right )\\\\\Rightarrow a_{n}-\frac{2}{n^2}=\frac{1}{2^{n-1}}\left ( a_{1}-\frac{2}{{1}^{2}} \right )
for 1st one oder way
a_{n+1}=2a_{n}+1\Longleftrightarrow a_{n+1}+1=2(a_{n}+1)
\therefore a_{n}+1=2^{n-1}(a_{1}+1)=3\cdot 2^{n-1},
threfore giving a_{n}=3\cdot 2^{n-1}-1\ (n\geq 1)